Adhesion and Aggregation of Thrombin Prestimulated Human Platelets on Surface-Bound Fibrinogen: Evidence for Involvement of ADP and Arachidonic Acid Pathways - Feuerstein, I A; Dickson, V M (Thrombosis and Haemostasis, 1983)
The purpose of this study was to examine the influence of substances released from human platelets upon their accumulation on human fibrinogen-coated glass tubes. After prestimulation with thrombin for one minute or in the absence of prestimulation, washed human platelets suspended in Eagle’s medium with RBC were drawn through the tubes at 1 ml/min, 80 s-1, for 1, 2 or 6 min. Thrombin prestimulation (0.02,0.05 or 0.25 U/ml) was followed by inactivation with hirudin (0.1, 0.25 or 1.25 U/ml) before flow. Singly adherent platelets were observed in the absence of thrombin or with thrombin for exposure times of 1 and 2 min. At 6 min after at least 0.05 U/ml of thrombin, surface- bound aggregates were observed. The initial rate of adhesion increased with the amount of thrombin used for prestimulation. For adhesion to fibrinogen in the absence of prestimulation, platelet-derived ADP was a stimulator. Adhesion was shown to be independent of the ADP and arachidonic acid pathways in response to prestimulation with a low level of thrombin, 0.02 U/ml. For adhesion and cohesion, aggregation, in the presence of sufficient thrombin for prestimulation, 0.05 U/ml, ADP, serotonin and substances from arachidonic acid metabolism acted jointly to stimulate platelets.
Keywords: Platelet adhesion; Platelet aggregation; Fibrinogen-binding; Thrombin